STUDENTS' STRATEGIES TO OVERCOME ENGLISH SPEAKING ANXIETY - Rizkiya, Ani; Pratolo, Bambang Widi (Universitas Muhammadiyah Metro, 2023)
Speaking anxiety appears detrimental to English learners since it can lead to negative self-perceptions, mental slowness, and poor performance. As a result, students cannot achieve a high degree of English competence, particularly fluency. English Education students at Universitas Ahmad Dahlan Yogyakarta experienced a fear of speaking because they find it challenging to communicate with lecturers and peers in English. This study investigates students' English-speaking anxiety levels, the factors that cause students' English-speaking anxiety, and the strategies the students use to overcome English-speaking anxiety. This qualitative study utilized questionnaires and interviews to answer the research questions and collect data. The questionnaire of 33 statements related to anxiety in speaking English; semi-structured interviews were used to collect the data for this study. Six students were interviewed, and 85 students in the third semester were respondents to the questionnaire, a random sample. This study found that 34 students had moderate anxiety levels, while the anxiety factors that influenced students were communication apprehension, test anxiety, and fear of negative evaluation. The students' strategies to reduce anxiety are preparation, positive thinking, relaxation, and peer seeking. Those strategies could reduce the students' English-speaking anxiety. The results of this study can be used as input for students who experience anxiety in speaking English and for English teachers to understand their students' anxiety better.